Seismic hazard analysis of Zarand city using ahp-gis - Kargaranbafghi, Fariba; Kheirandish Ravari, Maryam; Rahimi Shahid, Mojtaba (Italian journal of engineering geology and environment, 2020)
This paper presents a detailed study about the seismic pattern of Zarand County in Kerman province that is an area with a high risk of earthquakes in Iran. The population of the Zarand County is about 120000. There are numerous active faults in the region and the area has been hit by several strong earthquakes, two of which were most deadly during the last half-century.In this research, the seismotectonics and seismic hazard was evaluated by probabilistic and analytical methods in 1:100000 scale geological map of the Zarand. Seismic risk analysis using the Gutenberg-Richter law predicted the probability for an earthquake with a magnitude of 6.5 on the Richter scale in the area within the next 40 years, 100 percent. Based on the results, Zarand City is considered as a medium and high earthquake risk area. The highest percentage of earthquake hazard is located in the central and north and northeastern regions of Zarand's geological map. In this map, the area with a high risk and very high risk is 35.43% and 24.22% respectively.